Escalation in the Kunduz region: Who are the insurgents in Northeastern Afghanistan? - Guido Steinberg; Nils Wörmer (Stiftung Wissenschaft und Politik (SWP), 2010)
Although approximately 5,000 US soldiers were transferred into Northern Afghanistan in the first half of 2010 and there have been initial military successes, the intensity of the insurgency in the Kunduz region has not diminished. Instead, there has been a continuing escalation of violence there in recent months. The unabated strength of the insurgency is based primarily on highly diversified leadership and logistical structures. The insurgency in the northeast consists of several groups, which follow different strategic objectives, but maintain close tactical cooperation. The main groups are the Afghan Taliban, the Islamic Party of Gulbuddin Hekmatyar, and the Islamic Movement of Uzbekistan. Additional groups include the Haqqani Network and al-Qaeda. It is important to assemble precise information about the ideological and strategic characteristics of these groups as only then can effective military action be taken and only then can decisions be made about which groups must be approached as negotiation partners
Keywords: 320